Counselling in the introductory phase of studies - Malihe Brensing; Till Dannewald; Annika Kanzinger; Ulrike Mayer; Joerg Zender (Forum Neue Medien in der Lehre Austria, 2021)
The University of Applied Sciences RheinMain has a heterogenic field of beginners, which leads to a high dropout rate after the first semester. We ran a project to change the engineering department's introductory phase based on motor learning's feedback concept. The beginners could choose to have one exam at the end of the semester or having three shorter exams instead during the semester. Failing one of the shorter exams made it mandatory to get individual counselling. The data from that project shows the effects of that counselling which helps the students to be successful in later exams. Students, who assume early support offers, are proven to perform better.